Cosmetics
Patent Information
- Application Number
- JP2020164364
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-09-30
AI Technical Summary
【0007】 本発明によれば、特定アスペクト比および特定厚さの脂肪酸マグネシウム塩粒子を、そのアスペクト比および厚さを保ったまま製剤に配合しておくことで、製品形態の時にはキラキラしているが、塗布後はその脂肪酸マグネシウムが崩れて小さくなり、この脂肪酸マグネシウムが雲母の不自然なツヤを消して自然な仕上がり性を発揮する化粧料を提供することができる。
Smart Images

Figure 0007609594000001 
Figure 0007609594000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a cosmetic preparation containing magnesium fatty acid. [Background technology]
[0002] It is known that extender pigments are blended to maintain the formulation of cosmetics. Extender pigments are expected to function as diluents to adjust the spreadability, adhesion, gloss, etc., and to adjust the color tone.
[0003] Known extender pigments include inorganic pigments and organic pigments, and mica is known as one type of inorganic pigment (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-234133 A [Patent Document 2] JP 2006-199645 A Summary of the Invention [Problem to be solved by the invention]
[0005] Mica has been added in hopes of improving usability, but due to its plate-like particle size, as more is added, it imparts excess shine, making it difficult to achieve a natural finish. An object of the present invention is to provide a novel cosmetic preparation which is easy to use, has excellent appearance as a product, and provides a natural finish when applied. [Means for solving the problem]
[0006] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by including fatty acid magnesium salt particles having a specific aspect ratio and average thickness and mica. [1] A cosmetic comprising fatty acid magnesium salt particles and mica, The fatty acid of the fatty acid magnesium salt particles is 12 to 22. The fatty acid magnesium salt particles have an aspect ratio represented by the following formula (1) of 1.0 or more and 2.0 or less, The cosmetic preparation, wherein the fatty acid magnesium salt particles have an average thickness of 250 to 600 nm. Aspect ratio = long axis diameter of particle (μm) / short axis diameter of particle (μm) Equation (1) [2] The cosmetic preparation according to [1], wherein the content of the mica is 5% by mass or more. [3] The cosmetic material according to [1] or [2], wherein the mica comprises synthetic phlogopite. [4] The cosmetic preparation according to any one of [1] to [3], wherein the average particle size of the mica is 15 μm or less. Effect of the Invention
[0007] According to the present invention, by incorporating fatty acid magnesium salt particles having a specific aspect ratio and specific thickness into a formulation while maintaining that aspect ratio and thickness, it is possible to provide a cosmetic product that is sparkling when in product form, but the fatty acid magnesium breaks down and becomes smaller after application, and this fatty acid magnesium removes the unnatural shine of the mica, thereby providing a natural finish. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The cosmetic composition of the present invention contains specific fatty acid magnesium salt particles as a metal soap. The fatty acid magnesium salt particles of the present invention are composed of a divalent fatty acid magnesium salt having 12 to 22 carbon atoms. Such particles can be prepared by a double decomposition method in which a fatty acid alkali compound salt obtained by reacting a fatty acid having 12 to 22 carbon atoms with a monovalent alkali compound is reacted with a divalent magnesium salt in an aqueous solution.
[0009] The fatty acid as the raw material of the fatty acid alkali compound salt is not particularly limited as long as it is a fatty acid having 12 to 22 carbon atoms. That is, it may be either a naturally derived fatty acid or a synthetic fatty acid, either a saturated fatty acid or an unsaturated fatty acid, and either a straight-chain or a branched fatty acid. Furthermore, the fatty acid structure may contain functional groups such as a hydroxyl group, an aldehyde group, and an epoxy group. As the fatty acid, a straight-chain saturated fatty acid is preferable.
[0010] In addition, when the carbon number of the fatty acid is 12 or more, it is possible to impart excellent usability to the cosmetic preparation. On the other hand, when the carbon number is 22 or less, it is easy to obtain the fatty acid industrially, and the solubility in water of the obtained fatty acid alkali compound salt is not significantly reduced, so that the productivity is high. The carbon number of the fatty acid is preferably 12 to 18, and more preferably 14 (i.e., the fatty acid magnesium is magnesium myristate).
[0011] Examples of fatty acids include lauric acid, myristic acid, myristoleic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, arachic acid, behenic acid, erucic acid, hydroxystearic acid, and epoxystearic acid, among which myristic acid is preferred. When mixed fatty acids are used, the myristic acid content in the fatty acids is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more.
[0012] The fatty acid magnesium salt particles of the present invention have an aspect ratio of 1.0 or more and 2.0 or less, preferably 1.0 or more and 1.6 or less, and more preferably 1.0 or more and 1.5 or less. In the present invention, the aspect ratio of a particle corresponds to the following formula (1), that is, the value obtained by dividing the major axis diameter of a fatty acid magnesium salt particle by the minor axis diameter (=major axis diameter / minor axis diameter). Aspect ratio = long axis diameter of particle (μm) / short axis diameter of particle (μm) Equation (1) The closer the aspect ratio is to 1.0, the closer the particle shape is to a square or a circle. The fatty acid magnesium salt particles of the present invention preferably have a shape close to a square. This improves the spreadability on the skin and provides excellent usability.
[0013] The "major axis diameter" of a particle is the length of the major axis of the particle, more specifically, the width of the particle where the distance between the two parallel lines sandwiching the particle is maximum. The "minor axis diameter" of a particle is the length of the minor axis of the particle, more specifically, the width of the particle measured along a straight line passing through the midpoint of the major axis and perpendicular to the major axis. The average thickness of a particle is the average value obtained by measuring the side length of 10 particles when the surface with the largest area of the fatty acid magnesium salt particles is the front. The average thickness of a particle is a value measured based on a two-dimensional projection image of the particle (more specifically, a SEM photograph).
[0014] Moreover, the fatty acid magnesium salt particles of the present invention have an average particle thickness of 250 to 600 nm. With such a thickness, the particles are easily dissolved even under mild mixing conditions (production method) in cosmetics, and can be easily applied uniformly to the skin as a cosmetic, while improving the finish and feel after application. Furthermore, when the average thickness is 250 nm or more, the fatty acid magnesium salt particles have good handleability when added to cosmetics, and there is no risk of a decrease in workability. The average particle thickness is more preferably 280 to 450 nm, and particularly preferably 300 to 450 nm. If the average particle thickness is 300 to 450 nm, the action and effect of the present invention can be obtained even more stably.
[0015] The cosmetic of the present invention contains fatty acid magnesium salt particles having the above-mentioned specific properties, and thus has excellent appearance as a product. Specifically, the light reflected on the cosmetic surface appears to sparkle and shine (referred to as a "scattered" appearance in the present invention). This is presumably because the aspect ratio is specific, i.e., the shape is close to a square, and the particle thickness is small, so that mirror reflection is likely to occur on the particle surface, and a beautiful luster is imparted to the cosmetic. Furthermore, the cosmetic preparation of the present invention has excellent usability due to the inclusion of the fatty acid magnesium salt particles having the above-mentioned specific properties. This is presumably because the fatty acid magnesium salt particles of the present invention have a specific aspect ratio, which improves the spreadability on the skin.
[0016] In addition, since the fatty acid magnesium of the present invention is a soft metal soap, it easily disintegrates when applied to the skin and the particle size becomes small. Therefore, after application, specular reflection is less likely to occur, so excess gloss is suppressed and a natural finish can be achieved. In this way, the cosmetic of the present invention containing the fatty acid magnesium having a specific aspect ratio and thickness changes gloss when applied, suppressing excess gloss of mica and achieving a natural finish.
[0017] Furthermore, the fatty acid magnesium salt particles of the present invention preferably have a particle index of 1.5 or more and 8.0 or less. Such a particle index makes it easier to apply the fatty acid magnesium salt particles uniformly to the skin as a cosmetic, and the feeling after application can be maintained for a long time. Furthermore, if the particle index is 1.5 or more, the fatty acid magnesium salt particles have good dispersibility when added to a cosmetic, and there is no risk of a decrease in workability. The particle index of the particles is preferably 1.5 or more and 6.0 or less, and more preferably 2.0 or more and 5.0 or less. If the particle index is 2.0 or more and 5.0 or less, the effect of the present invention can be obtained even more stably. In the present invention, the particle index of a particle corresponds to the following formula (2), i.e., the value obtained by dividing the major axis diameter of a fatty acid magnesium salt particle by the minor axis diameter (=major axis diameter / minor axis diameter) by the average thickness of the particle [=(major axis diameter / minor axis diameter) / average thickness of the particle]. Particle index = [(major axis diameter of particle (μm) / minor axis diameter of particle (μm)) / average thickness of particle (nm)] × 1000 Equation (2)
[0018] Furthermore, the fatty acid magnesium salt particles of the present invention have a narrow particle size distribution, which allows them to be uniformly present in a cosmetic, and the effects of the present invention (particularly, improved feel of the cosmetic) are more likely to be exhibited stably. Specifically, the fatty acid magnesium salt particles preferably have a median diameter of 10.0 to 40.0 μm, and a particle size summary value A represented by the following formula (3) is preferably 2.5 or less. Grain size summary value A = (D90 - D10) / D50... formula (3) (However, 10.0≦D50≦40.0) D10: 10% cumulative diameter (μm) of fatty acid magnesium salt particles on a volume basis D50: Median diameter of fatty acid magnesium salt particles on a volume basis (μm) D90: 90% cumulative diameter (μm) of fatty acid magnesium salt particles on a volume basis
[0019] In the present invention, the particle size summary value A is calculated from the particle size measured by a microtrack laser diffraction method. When the particle size summary value A is 2.5 or less, the particle size of the fatty acid magnesium salt particles present in the cosmetic becomes uniform, the dispersibility of the cosmetic is good, the productivity does not decrease, and a cosmetic having the desired feel can be produced. It is more preferable that the particle size summary value A satisfies the relationship of 0.5≦A≦2.5. When the relationship of 0.5≦A≦2.5 is satisfied, the action and effect of the present invention can be obtained even more stably. When the particle size summary value A is 0.5 or more, the yield does not decrease and the production can be stably carried out on an industrial scale. In addition, when the cumulative curve is calculated by the above formula (3) with the total volume of the powder group being 100%, the particle diameters at the points where the cumulative curve is 10%, 50%, and 90% are the 10% cumulative diameter (D10), 50% median diameter (D50; median diameter), and 90% cumulative diameter (D90) (μm), respectively. Note that particle diameter means the particle diameter of the primary particle. If the particles are aggregated during measurement, they are measured in a dispersed state using ultrasound or the like.
[0020] The particle size summary value A can be adjusted by appropriately adjusting the concentration of the fatty acid alkali compound salt, the temperature during the reaction between the fatty acid alkali compound salt and the magnesium salt, and the dripping speed when the aqueous solution containing the magnesium salt is dripped into the aqueous solution containing the fatty acid alkali compound salt. In addition, for those with a wide particle size distribution, that is, those with a large value of the particle size summary value A, the particle size summary value A can be adjusted in the post-treatment by classification using sieves of 100 mesh, 200 mesh, 330 mesh, etc.
[0021] The microtrack laser diffraction method used here is a method for determining particle size distribution by utilizing scattered light obtained by irradiating particles with laser light. In the present invention, a wet measurement is performed in which a sample is introduced into a circulating organic solvent in which fatty acid magnesium salt particles are not dissolved, such as ethanol or isopropyl alcohol. The particle diameters of the particles to be measured in the present invention are in the range of 0.1 μm to 200 μm, and the value represented by the above formula (1) is taken as the particle size summary value A. In the present invention, the measurement can be performed using, for example, Microtrack MT-3000 manufactured by Nikkiso Co., Ltd.
[0022] The fatty acid magnesium salt particles of the present invention preferably have a volume-based median diameter (D50) of 10.0 to 40.0 μm. Such a particle diameter provides a good feel when used. The fatty acid magnesium salt particles preferably have a median diameter of 13.0 to 35.0 μm, more preferably 15.0 to 25.0 μm. The particle diameter can be measured by a microtrack laser diffraction method in the same manner as the particle size summary value A described above.
[0023] The shape of the fatty acid magnesium salt particles of the present invention is not particularly limited, but from the viewpoint of usability, a plate shape is preferable.
[0024] To obtain fatty acid magnesium salt particles that satisfy the above-mentioned specific properties, the fatty acid magnesium salt particles can be prepared by a metathesis method in which a fatty acid alkali compound salt obtained by reacting a monovalent alkali compound with a fatty acid having 12 to 22 carbon atoms is reacted with a divalent magnesium salt in an aqueous solution. When mixing the magnesium salt-containing aqueous solution and the fatty acid alkali compound salt-containing aqueous solution that have been separately prepared by the metathesis reaction, it is preferable to gradually drop the magnesium salt-containing aqueous solution into the fatty acid alkali compound salt-containing aqueous solution, as described below.
[0025] Examples of monovalent alkali compounds that can be used as raw materials for fatty acid alkali compound salts include hydroxides of alkali metals (sodium, potassium, etc.), and amines such as ammonia, monoethanolamine, diethanolamine, triethanolamine, etc. Preferred are hydroxides of alkali metals such as sodium and potassium, because they have high solubility in water when made into fatty acid alkali compound salts.
[0026] The fatty acid alkali compound salt used in the present invention is obtained by reacting a monovalent alkali compound with a fatty acid at a temperature that is generally equal to or higher than the melting point of the fatty acid and at a temperature at which the fatty acid does not decompose, preferably 100°C or lower, more preferably 50 to 100°C, even more preferably 60 to 95°C, and particularly preferably 80 to 95°C.
[0027] The fatty acid magnesium salt particles of the present invention can be obtained, for example, by reacting the fatty acid alkali compound salt obtained above with a magnesium salt in an aqueous solution. The magnesium salt is specifically a salt of inorganic magnesium with an inorganic acid or an organic acid. Examples of the magnesium salt include magnesium chloride, magnesium sulfate, and magnesium acetate. In particular, magnesium chloride and sulfate are preferred because they have high solubility in water and react efficiently with the fatty acid alkali compound salt.
[0028] The reaction between the fatty acid alkali compound salt and the divalent magnesium salt is specifically carried out by separately preparing an aqueous solution containing the magnesium salt and an aqueous solution containing the fatty acid alkali compound salt, and then mixing them together, for example by adding the aqueous solution containing the magnesium salt to the aqueous solution containing the fatty acid alkali compound salt, or by adding both to separate reaction vessels.
[0029] When mixing the aqueous solution containing the fatty acid alkali compound salt with the aqueous solution containing the magnesium salt, for example, if the aqueous solution containing the magnesium salt is added to the aqueous solution containing the fatty acid alkali compound salt all at once, the shape of the resulting fatty acid magnesium salt particles may become non-uniform, and the aspect ratio of the particles may become large. Therefore, in the present invention, it is preferable to gradually drop the aqueous solution containing the magnesium salt into the aqueous solution containing the fatty acid alkali compound salt at an appropriate speed.
[0030] The dropping speed is preferably 0.005 to 0.8 mol / min per unit time, more preferably 0.01 to 0.5 mol / min. By mixing at such a dropping speed, the exchange reaction between alkali and magnesium can proceed gently, and fatty acid magnesium salt particles having an appropriate aspect ratio and thickness can be obtained. When this speed is 0.005 mol / min or more, fatty acid magnesium salt particles having a desired aspect ratio and thickness can be obtained. On the other hand, when the dropping speed per unit time is 0.8 mol / min or more or less, the fatty acid magnesium salt particles have a uniform shape and the particles have the desired aspect ratio and thickness, so that the particle size is not uneven and is good. The unit of "mol / min or more" for the magnesium salt to be added dropwise is the number of moles of magnesium salt to be added dropwise per unit time per 1 mole of fatty acid alkali compound.
[0031] The concentration of the fatty acid alkali compound salt during the production of the fatty acid magnesium salt is usually 1% by mass to 20% by mass, preferably 5% by mass to 15% by mass, from the viewpoint of the productivity of the fatty acid magnesium salt and the handling properties of the fatty acid alkali compound salt-containing aqueous solution or the fatty acid magnesium salt slurry obtained. If the concentration of the fatty acid alkali compound salt is 1% by mass or more, the productivity of the fatty acid magnesium salt is good, which is preferable. If it is 20% by mass or less, the viscosity of the fatty acid alkali compound salt-containing aqueous solution or the fatty acid magnesium salt slurry obtained does not increase, and a uniform reaction can be performed. The concentration of the magnesium salt in the magnesium salt-containing liquid is usually 10% by mass to 50% by mass, preferably 10% by mass to 40% by mass, from the viewpoint of the productivity of the fatty acid magnesium salt and the handling properties of the fatty acid alkali compound salt-containing aqueous solution or the fatty acid magnesium salt slurry obtained.
[0032] The reaction between the fatty acid alkali compound salt and the magnesium salt is carried out under temperature conditions that are generally used by those skilled in the art, taking into consideration the solubility of the fatty acid alkali compound salt, preferably 50 to 100° C., more preferably 60 to 95° C. If the reaction temperature is 50° C. or higher, the reaction rate between the fatty acid alkali compound salt and the magnesium salt is good.
[0033] In order to stabilize the fatty acid magnesium salt slurry during the reaction of the fatty acid alkali compound salt with the magnesium salt and improve the productivity of the fatty acid magnesium salt, it is preferable to make a polyalkylene glycol ether, particularly a triblock ether having a structure (EO-PO-EO) in which an oxypropylene block is sandwiched between oxyethylene blocks, present in the fatty acid magnesium salt slurry. The content of the polyalkylene glycol ether in the fatty acid magnesium salt slurry is usually 0.01 to 5 parts by mass, preferably 0.05 to 2 parts by mass, per 100 parts by mass of the fatty acid alkali compound salt. The polyalkylene glycol ether may be present in the reaction system before the monovalent alkali compound is reacted with the fatty acid, or may be present in the reaction system before the reaction of the fatty acid alkali compound with the magnesium salt.
[0034] By this method, a fatty acid magnesium salt cake with reduced moisture content is obtained by separation using a dehydrator, a filter press, etc. The fatty acid magnesium salt cake with reduced moisture content is dried using a rotary dryer, an airflow dryer, a ventilated tray dryer, a vacuum tray dryer, a spray dryer, a fluidized bed dryer, etc.
[0035] In the present invention, the fatty acid magnesium salt cake must be dried at (α-60)°C≦α≦(α-30)°C relative to the water vaporization peak top temperature (α°C) of the fatty acid magnesium salt produced. Here, the water vaporization peak top temperature refers to the top peak of the temperature range at which the residual water contained in the fatty acid magnesium salt that cannot be removed by the drying begins to desorb. For example, in the heat absorption graph of magnesium myristate by differential scanning calorimetry (DSC), the water vaporization peak top temperature is 102.1°C. The specific drying temperature varies depending on the type of fatty acid magnesium salt obtained, but for example, in the case of magnesium myristate, it is 72°C or lower. If the drying process is performed at a temperature higher than 72°C, fine particles will adhere to each other, and the thickness of the particles will tend to increase. On the other hand, if the drying process is performed at a temperature lower than 40°C, the drying property will decrease, and a large amount of water will tend to remain in the compound, which may result in a decrease in productivity. The fatty acid magnesium salt particles can be produced as described above.
[0036] The content of the fatty acid magnesium in the cosmetic of the present invention is preferably 1 to 30% by mass, more preferably 5 to 30% by mass, from the viewpoints of the beautiful appearance of the preparation and of eliminating the unnatural luster of mica.
[0037] The cosmetic of the present invention further contains mica, which improves the ease of use of the cosmetic. The ease of use here specifically means that the cosmetic has a smooth and good feel when applied. From the viewpoint of achieving a natural finish when applied, it is preferable that the particle size of the mica is not too large, and the average particle size is preferably 15 μm or less. From the viewpoint of achieving a natural finish, it is even more preferable that the average particle size is 10 μm or less. The average particle size can be measured, for example, by using a laser diffraction / scattering type particle size distribution analyzer, and means D50.
[0038] As the mica, from the viewpoint of better usability, natural mica, synthetic phlogopite, and synthetic ferric phlogopite are preferred, and synthetic phlogopite is particularly preferred. These can be used alone or in combination of two or more kinds.
[0039] The content of mica in the cosmetic of the present invention is preferably 5% by mass or more, more preferably 5% by mass to 50% by mass, and more preferably 15% by mass to 35% by mass, from the viewpoint of a smooth feel when used.
[0040] The cosmetic of the present invention may further contain an inorganic powder and an organic powder. Examples of inorganic powders include inorganic pigments such as zinc oxide, red iron oxide, yellow iron oxide, and black iron oxide, as well as talc. The organic powder includes organic pigments such as natural dyes. Furthermore, these powders may be surface-treated with a fluorine compound, a silicone compound, a fatty acid, or the like.
[0041] The cosmetic preparation of the present invention may further contain an oily component. The oil component may be a liquid oil component or a solid oil component. When the cosmetic of the present invention is used as a powder cosmetic, a liquid oil component is preferred from the viewpoint of reducing powder aggregation and product stability.
[0042] Examples of liquid oily components include silicone oils, avocado oil, camellia oil, macadamia nut oil, corn oil, olive oil, rapeseed oil, egg yolk oil, sesame oil, persic oil, wheat germ oil, sasanqua oil, castor oil, linseed oil, safflower oil, cottonseed oil, perilla oil, soybean oil, peanut oil, tea seed oil, kaya oil, rice bran oil, Chinese tung oil, Japanese tung oil, jojoba oil, germ oil, triglycerin, glycerin trioctanoate, glycerin triisopalmitate, etc. These may be used in combination of two or more kinds.
[0043] Examples of solid oily components include solid paraffin, ceresin, microcrystalline wax, polyethylene wax, hardened oil, beeswax, Japan wax, candelilla wax, and other hydrocarbon waxes, higher fatty acids such as stearic acid, lauric acid, myristic acid, and behenic acid, and higher alcohols such as cetyl alcohol, stearyl alcohol, and lauryl alcohol. Two or more of these may be used in combination.
[0044] From the viewpoint of usability, the content of the oily component in the cosmetic is preferably 1 to 15 mass %, more preferably 5 to 10 mass %.
[0045] In addition to the above-mentioned components, the cosmetic preparation of the present invention may contain other components depending on the purpose within the quantitative and qualitative ranges that do not impair the effects of the present invention. For example, colorants, pH adjusters, moisturizers, thickeners, surfactants, dispersants, stabilizers, colorants, preservatives, antioxidants, sequestering agents, astringents, anti-inflammatory agents, ultraviolet absorbing agents, fragrances, and other pigments may also be appropriately blended within the range that achieves the purpose of the present invention.
[0046] The cosmetic composition of the present invention may be used in any form, such as powder, powder solid, cream, milk, lotion, oily liquid, oily solid, or paste.
[0047] The uses of the cosmetics include, for example, makeup cosmetics such as makeup base, foundation, concealer, face powder, control color, sunscreen cosmetics, lipstick, lip balm, eye shadow, eyeliner, mascara, cheek color, nail polish, body powder, perfume powder, and baby powder, as well as skin care cosmetics and hair care cosmetics. EXAMPLES
[0048] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. Unless otherwise specified, the blending amount of each component is expressed as mass % based on the system in which the component is blended.
[0049] [Preparation of magnesium myristate 1] A 10L separable flask was charged with 500g of myristic acid (NOF Corp. NAA-142) and 5600g of water, and the temperature was raised to 90°C. Next, 250.0g of 48% by mass sodium hydroxide aqueous solution was added, and the mixture was stirred at the same temperature (90°C) for 1 hour to obtain an aqueous solution of fatty acid alkali compound salt. Then, while maintaining the temperature at 90°C, 750.0g of 22% by mass magnesium sulfate aqueous solution was dropped into the aqueous solution of sodium myristate over 40 minutes [dropping rate: 0.016 (mol / min)]. After the dropwise addition, the mixture was kept at 90°C and stirred for 30 minutes to mature. The resulting aqueous solution of fatty acid magnesium salt was cooled to 65°C or lower. Then, the mixture was filtered with a suction filter, washed with 1000g of water 8 times, and the resulting cake was dried at 60°C using a ventilated tray dryer, and crushed with a mill to obtain magnesium myristate particles.
[0050] [Preparation of magnesium myristate 2] 200g of myristic acid (NOF Corp., NAA-142), 1.00g of polyethylene glycol-polypropylene glycol-block ether (NOF Corp., trade name: Pronon #104) and 2500g of water were charged into a 3L separable flask and heated to 80°C. Next, 73.6g of 48% by mass sodium hydroxide aqueous solution was added and stirred at the same temperature (80°C) for 30 minutes to obtain an aqueous solution of sodium myristate. After that, while maintaining the temperature at 80°C, 253.8g of 22% by mass magnesium sulfate aqueous solution was dropped into the aqueous solution of sodium myristate over 40 minutes [dropping rate: 0.013 (mol / min)]. After the dropwise addition, the mixture was kept at 80°C and stirred for 30 minutes to mature. The resulting aqueous solution of magnesium fatty acid salt was allowed to cool to 60°C or less. Thereafter, the mixture was filtered using a suction filter and washed twice with 1000 g of water. The resulting cake was dried at 60° C. using a ventilated tray dryer and crushed in a mill to obtain magnesium myristate particles.
[0051] [Evaluation of Magnesium Myristate Particles] For magnesium myristate particles 1 and 2, the median diameter, particle size summary value A [value calculated from the 10% cumulative diameter on a volume basis D10 (μm), the median diameter on a volume basis D50 (μm), and the 90% cumulative diameter on a volume basis D90 (μm)], average particle thickness, major axis diameter, minor axis diameter, and aspect ratio were measured using the following devices and the methods described above.
[0052] (1) Grain size summary value A, median diameter 2.0 g of sample was placed in a 100 ml glass beaker, and 3 to 5 ml of a nonionic surfactant (e.g., NOF Corp.'s Nonion NS-210) was dropped onto it and mixed with a spatula. Next, 20 ml of purified water was added, and the mixture was dispersed by ultrasonic waves to make a 100 ml volume to be used as the measurement sample. The sample was fed into a particle size distribution measuring device (equipment name: "Microtrac MT-3000", Nikkiso Co., Ltd.) and measured (principle: laser diffraction and scattering method). When a cumulative curve was calculated assuming the total volume of the powder mass to be measured as 100%, the particle sizes at the points where the cumulative curve was 10%, 50%, and 90% were calculated as the 10% diameter (D10), 50% diameter (D50; median diameter), and 90% diameter (D90) (μm), respectively. The particle size summary value A was calculated from the obtained D10, D50, and D90.
[0053] (2) Average particle thickness, major axis diameter, minor axis diameter, aspect ratio, particle index The thickness of the particles was measured using a scanning electron microscope by the following method. After fatty acid magnesium salt particles were attached to double-sided carbon tape, the particle surfaces were coated with platinum particles by vapor deposition, and the sample was observed at an acceleration voltage of 1.0 kV and a magnification of 2000 times, and the thickness of any particle was measured. The thickness, major axis diameter, and minor axis diameter were determined for 10 randomly selected particles. The aspect ratio and particle index were calculated using the following formulas. Particle index = [(major axis diameter (μm) / minor axis diameter (μm)) / average thickness of particles (nm)] × 1000 Aspect ratio = major axis diameter (μm) / minor axis diameter (μm)
[0054] The results of the above measurements are shown below. <Properties of magnesium myristate particles 1> Aspect ratio: 1.4 Particle index: 4.7 D10: 11.4 μm D50: 25.3μm D90: 54.9μm Average particle thickness: 309 nm Grain size summary value A: 1.7
[0055] <Properties of magnesium myristate particles 2> Aspect ratio: 1.0 Particle index: 2.4 D10: 9.8μm D50: 19.1μm D90: 34.0μm Average particle thickness: 424nm Grain size summary value A: 1.3
[0056] [Magnesium myristate 3] For comparison, magnesium myristate (manufactured by Taihei Chemical Industry Co., Ltd.) with an aspect ratio of 2.52 and a median diameter (D50) of 17 μm was prepared.
[0057] <Examples 1 to 6 and Comparative Example 1: Pressed Powder> A pressed powder having the composition shown in Table 1 was prepared according to the following manufacturing method. Manufacturing method: The powders excluding the oil and magnesium myristate were mixed using a Henschel mixer, and after adding the oil, the mixture was mixed again using the mixer. After mixing, the mixture was pulverized using a grinder. The mixture was then returned to the mixer, magnesium myristate was added, and the mixture was gently mixed. The resulting mixture was filled into an inner plate and molded.
[0058] [Usability evaluation] The cosmetic preparation (pressed powder) obtained according to the present invention was evaluated for appearance, feel during use, etc., based on the following criteria. The results are shown in Table 1. (1) Appearance Five expert panelists judged the dotted appearance of the finished product as follows, and rated the appearance as good when it was rated 3 to 5. The dotted appearance refers to a state in which the surface is sparkling due to reflection. 5: There is a strong sense of dottedness 4: There is a noticeable sense of scattering 3: There is a slight sense of scattering 2: Not much of a scattered feel 1: No scattered feeling
[0059] (2) Smooth feel when used Five expert panelists judged the smoothness of the cosmetic preparations when applied to the skin as follows, and rated the smoothness as good when it was rated 3 to 5. 5: Very smooth 4: Quite smooth 3: Slightly smooth 2: Not very smooth 1: Not smooth
[0060] (3) Natural finish Five expert panelists judged the finish of the cosmetic product when applied to the skin as follows, and rated a score of 3 to 5 as a good natural finish. 5. The finish is very natural 4: The finish is quite natural 3: The finish is natural 2: The result is slightly unnatural 1: The finish is unnatural
[0061] [Table 1]
[0062] (*1) PDM-FE manufactured by Topy Industries Ltd. (*2) Topy Industries PDM-5L (*3) Topy Industries PDM-10L (*4) Y-1800 manufactured by Yamaguchi Mica Co., Ltd. (*5) Satinia M-5 manufactured by JGC Catalysts and Chemicals Co., Ltd.
[0063] The above results show that cosmetics containing magnesium myristate particles having specific properties and mica have excellent appearance and feel when used.
[0064] Example 7: Loose Powder A loose powder having the composition shown in Table 2 was prepared according to the following manufacturing method. Manufacturing method: All powders except magnesium myristate were mixed using a mixer. Magnesium myristate was added to the mixed powders and mixed gently. The resulting mixture was filled into a container with a mesh. The evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2 below.
[0065] [Table 2]
[0066] (*2) Topy Industries PDM-5L
[0067] As shown in the above table, it can be seen that cosmetics containing magnesium myristate and mica with specific properties have excellent appearance and usability, and also have excellent finish when applied.
Claims
1. A cosmetic comprising fatty acid magnesium salt particles and mica, The average particle size of the mica is 15 μm or less, the fatty acid of the fatty acid magnesium salt particles has 12 to 22 carbon atoms; The fatty acid magnesium salt particles have an aspect ratio represented by the following formula (1) of 1.0 or more and 2.0 or less, The fatty acid magnesium salt particles have an average thickness of 250 to 600 nm; The cosmetic contains the fatty acid magnesium salt particles in an amount of 1 to 30% by mass. Aspect ratio=major axis diameter of particle (μm) / minor axis diameter of particle (μm) Equation (1)
2. The cosmetic preparation according to claim 1 , wherein the content of the mica is 5% by mass or more.
3. The cosmetic preparation according to claim 1 or 2, wherein the mica comprises synthetic phlogopite.
Citation Information
Patent Citations
Colored cosmetic composition
JP1994172128A
Cosmetic use of hard gels and cosmetic or dermatological compositions using them
JP1999502867A
Cosmetic preparation for makeup
JP2000169340A
Cosmetic
JP2003267815A
Powder cosmetic
JP2006199645A